Can growth inhibition assays (GIA) predict blood-stage malaria vaccine efficacy? - Duncan, C; Hill, A; Ellis, R (2012)
An effective vaccine against P. falciparum malaria remains a global health priority. Blood-stage vaccines are an important component of this effort, with some indications of recent progress. However only a fraction of potential blood-stage antigens have been tested, highlighting a critical need for efficient down-selection strategies. Functional in vitro assays such as the growth/invasion inhibition assays (GIA) are widely used, but it is unclear whether GIA activity correlates with protection or predicts vaccine efficacy. While preliminary data in controlled human malaria infection (CHMI) studies indicate a possible association between in vitro and in vivo parasite growth rates, there have been conflicting results of immunoepidemiology studies, where associations with exposure rather than protection have been observed. In addition, GIA-interfering antibodies in vaccinated individuals from endemic regions may limit assay sensitivity in heavily malaria-exposed populations. More work is needed to establish the utility of GIA for blood-stage vaccine development.